A retrospective study on sex disparities and risk factors in acute ischemic stroke in the West bank of Palestine - Ahmed khraiwesh; Osama Ikhdour; Zainab Alalyat; Basma Damiri; Ahmad Abuhassan; Mohammad Abuawad (Scientific Reports)
Abstract Acute ischemic stroke (AIS) is one of the leading causes of mortality and morbidity. This study aimed to identify risk factors, subtypes, and associated outcomes of AIS in the West Bank based on sex. We retrospectively analyzed medical records from 2018 to 2022 of stroke patients from four main hospitals in the West Bank (N = 711). The Modified Rankin Scale (mRS) assessed post-stroke disability on presentation day and thirty days later based on patient history and physical examination findings. An adjusted multinomial logistic regression model was implemented to calculate the adjusted odds ratios (OR) and the 95% confidence interval (CI). The significance level was set at P < 0.05. Out of 711 records, 118 were excluded. The final analysis included 593 AIS patients, with a median age of 63 and an interquartile range of 15. The majority of the patients (60.37%) were males and most of them (62.1%) were smokers. Males were less likely to have diabetes mellitus (DM) (P = 0.037, OR = 0.691) and atrial fibrillation (P = 0.039, OR = 0.627) compared to females. Small-volume strokes accounted for the majority of cases (60.7%). AIS had a thrombotic cause in (81.9%) of patients. On presentation, (40.4%) and (37.2%) of patients had more severe symptoms with mRS scores of 4 and 3, respectively. Males were more likely than females (P = 0.018, OR = 2.03) to present with more severe symptoms (mRS 3-4-5) on day one. An increase of one year in age resulted in a 9.8% higher risk of death (mRS 6) on day one (P = 0.016, OR = 1.098). Smoking history was associated with a seven-fold increase in mortality on day one (P = 0.049, OR = 7.396). Males developed AIS at a younger age while DM and atrial fibrillation were significantly more common in females. The majority of patients reported more severe symptoms on presentation, with notable differences observed between sexes. Male patients exhibited a higher prevalence of severe symptoms compared to female patients. Additionally, key risk factors such as smoking was significantly associated with the severity of symptoms at presentation, with variations observed across sexes. Prevention of risk factors (e.g., HTN, DM, atrial fibrillation, and smoking) is crucial, and further research is required.